Metformin attenuates central sensitization by regulating neuroinflammation through the TREM2-SYK signaling pathway in a mouse model of chronic migraine - Zhenzhen Fan; Dandan Su; Zi Chao Li; Songtang Sun; Zhaoming Ge (Journal of Neuroinflammation)
Abstract Background Chronic migraine (CM) is a serious neurological disorder. Central sensitization is one of the important pathophysiological mechanisms underlying CM, and microglia-induced neuroinflammation conduces to central sensitization. Triggering receptor expressed on myeloid cells 2 (TREM2) is presented solely in microglia residing within the central nervous system and plays a key role in neuroinflammation. Metformin has been shown to regulate inflammatory responses and exert analgesic effects, but its relationship with CM remains unclear. In the study, we investigated whether metformin modulates TREM2 to improve central sensitization of CM and clarified the potential molecular mechanisms. Methods A CM mouse model was induced by administration of nitroglycerin (NTG). Behavioral evaluations were conducted using von Frey filaments and hot plate experiments. Western blot and immunofluorescence techniques were employed to investigate the molecular mechanisms. Metformin and the SYK inhibitor R406 were administered to mice to assess their regulatory effects on neuroinflammation and central sensitization. To explore the role of TREM2-SYK in regulating neuroinflammation with metformin, a lentivirus encoding TREM2 was injected into the trigeminal nucleus caudalis (TNC). In vitro experiments were conducted to evaluate the regulation of TREM2-SYK by metformin, involving interventions with LPS, metformin, R406, siTREM2, and TREM2 plasmids. Results Metformin and R406 pretreatment can effectively improve hyperalgesia in CM mice. Both metformin and R406 significantly inhibit c-fos and CGRP expression in CM mice, effectively suppressing the activation of microglia and NLRP3 inflammasome induced by NTG. With the administration of NTG, TREM2 expression gradually increased in TNC microglia. Additionally, we observed that metformin significantly inhibits TREM2 and SYK expression in CM mice. Lv-TREM2 attenuated metformin-mediated anti-inflammatory responses. In vitro experiments, knockdown of TREM2 inhibited LPS-induced SYK pathway activation and alleviated inflammatory responses. After the sole overexpression of TREM2, the SYK signaling pathway is activated, resulting in the activation of the NLRP3 inflammasome and an increased expression of pro-inflammatory cytokines; nevertheless, this consequence can be reversed by R406. The overexpression of TREM2 attenuates the inhibition of SYK activity mediated by metformin, and this effect can be reversed by R406. Conclusions Our findings suggest that metformin attenuates central sensitization in CM by regulating the activation of microglia and NLRP3 inflammasome through the TREM2-SYK pathway. Graphical Abstract